Attitudes of Facebook and Instagram Users Towards SNS Clothing Brands’ Posts and Their Influence on Users’ Purchasing - Karahasan, Tahsin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This case study has focused on the attitudes of individuals towards clothing brands posts in Facebook and Instagram, their influence on Terranova and Calliope brands and how these posts in Facebook and Instagram motivate SNS users, purchasing decisions. The research has been conducted with respondents who belong to different age categories and administered in three areas of Northern Cyprus; Nicosia, Morphou and Kyrenia. By using quantitative research methodology, an in-house questionnaire comprising 52 questions was prepared and 315 participants responded. The results of the study indicate that depending on their age, attitudes of individuals towards clothing brands’ posts in Facebook and Instagram show difference. Also, their reactions and encouragement they obtained from SNS posts as well as their motivation for their purchase decision, revealed statistically significant difference regarding their ages. The study indicates that the content of the SNS posts, like audio, video effects, colors, pictures, gestures and information, the price detail about the product are effective to take individuals’ attention for SNS posts. Regardless of individuals’ age, benefits of advertising in Facebook and Instagram, following the favorite clothing brands in SNS and the importance of the content of SNS posts for its efficiency were the common points that they attitude mutually.

ÖZ: Bu çalışma, Facebook ve Instagram kullanıcılarının SPS (Sosyal Paylaşım Siteleri) de yer alan giyim markaları reklamlarına karşı sergiledikleri tutumları, SPS yer alan reklamların kullanıcıları satın alma kararında nasıl motive ettiği, kullanıcı tutumlarının Terranova ve Calliope markalarının üzerindeki etkisi ölçmek üzere yürütülmüştür. Araştırma çalışması, Kuzey Kıbrıs da Lefkoşa, Gazimağusa ve Girnede, farklı yaş gruplarından bireyler üzerinde uygulanmıştır, Çalışmanın konusuna bağlı olarak nicel araştırma metodu kullanılan bir anket çalışması yürütülmüştür. Anket çalışması için 52 soru hazırlanmıştır. Sorular 9 çoktan seçmeli ve 43 likert ölçekli ifadelerden oluşmaktadır. 315 katılıımcı uygunluklarına göre soruları cevaplamıştır. Araştırmanın sonucu, bireylerin Facebook ve Instagramda yer alan giyim markaları reklamlarına karşı yaş değişkenliğine bağlı olarak farklı tutumlar sergilemişlerdir. Aynı zamanda, SPS de yer alan reklamların bireylerin satın alma kararları üzerinde motivasyon etkisi yine yaşa bağlı olarak farklı gözlemlenmiştir. Bunun yanısıra, araştırmada, SPS de yer alan reklamların- ses, görsellik, video renk, resim, kullanılan objeler gibi- içeriği ve ürün hakkında detaylı bilgi vermesi, ürünün fiyatının belirtilmesi gibi içeriklerin SPS kullanıcıları üzerinde dikkat çekmesi açısından etkili olduğu orta çıkmıştır. Yaş farkı gözetmeksizin, katılımcılar ortak bir şekilde giyim markalarının facebook ve instagram da reklam vermesini markalar açısından kullanıcılarda etkili olduğunu ve bu reklamların içeriğinin SPS kullanıcıları üzerinde satın alma sürecinde etkisi olduğunu belirtmişlerdir.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2018. Supervisor: Assoc. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Internet marketing--Social Networking Sites--Facebook--Adevertisements; Internet advertising--Online social networks--Facebook; Social media--Marketing--Internet marketing--Social marketing; Facebook; Instagram; Social Network Sites Posts; Terranova; Calliope